1992
DOI: 10.1111/j.1432-1033.1992.tb17285.x
|View full text |Cite
|
Sign up to set email alerts
|

10N‐Nonyl acridine orange interacts with cardiolipin and allows the quantification of this phospholipid in isolated mitochondria

Abstract: The acridine orange derivative, l0N-nonyl acridine orange, is an appropriate marker of the inner mitochondrial membrane in whole cells. We use membrane model systems to demonstrate that 10N-nonyl acridine orange binds to negatively charged phospholipids (cardiolipin, phosphatidylinositol and phosphatidylserine). The stoichiometry has been found to be 2 mol 10N-nonyl acridine orange/ mol cardiolipin and 1 mol dye/mol phosphatidylscrine or phosphatidylinositol, while, with zwitterionic phospholipids, significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
271
1
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(289 citation statements)
references
References 40 publications
9
271
1
3
Order By: Relevance
“…This indicates that the organelle structure was preserved, since NAO labels mitochondria independent of DC m 24 via an interaction with cardiolipin. 25 Using Western blots, we demonstrated that cytochrome c was released into the cytosol immediately after the irradiation of porphycene-sensitized cells at 108C ( Figure 2). The control (lane A) provides an estimate of the extent of mitochondrial contamination and/or base-line mitochondrial damage in the cell extracts used in this assay.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the organelle structure was preserved, since NAO labels mitochondria independent of DC m 24 via an interaction with cardiolipin. 25 Using Western blots, we demonstrated that cytochrome c was released into the cytosol immediately after the irradiation of porphycene-sensitized cells at 108C ( Figure 2). The control (lane A) provides an estimate of the extent of mitochondrial contamination and/or base-line mitochondrial damage in the cell extracts used in this assay.…”
Section: Resultsmentioning
confidence: 99%
“…29 LoVo cells were detached with EDTA/trypsin, then washed, centrifuged and resuspended in complete F12 medium. Cells (5 ϫ 10 5 /ml) were labeled with 20 nM NAO for 30 min at 37°C and after washing with cold PBS, samples were investigated by flow cytometry.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…However, R1a-myc-PRDX3AS cells show a minimal increase in reactive oxygen species. Analysis of mitochondrial mass with 10-N-nonyl-acridine orange (NAO) (27) reveals that MCF7͞ADR-PRDX3AS cells show decreased mitochondrial mass, whereas R1a-myc-PRDX3AS cells also show a small percentage of cells with reduced mitochondrial mass. Reduction of PRDX3 in both cell lines results in a decrease in mitochondrial membrane potential, indicated by the reduced uptake of 3,3Ј-dihexyloxacarbocyanine iodide (DiOC 6 ), as shown in Fig.…”
Section: Effect Of Prdx3 On Proliferation and Apoptosis In Mcf7͞adr Cmentioning
confidence: 99%